Construction of a vector for stable chromosomal integration of a Bacillus licheniformis phytase gene - Fernández, Maria Teresa (2009)
Phytases are a special class of phosphatases that catalyze the sequential hydrolysis of phytate. The inability of plants to utilize phosphorous from soil phytates is due to the low phytase activity in plant roots. Soil microorgan- isms play an important role in the processes that affect the transformation of phosphate containing compounds. Many of them can solubilize phosphorus from phytates, by means of the liberation of phytases. This process allows the mobilization of phosphorus towards the plants and a better utilization of this nutrient. Nevertheless, many soil bacteria lack gene coding for these enzymes, which diminishes the availability of this element in soil. One alternative to obtain improved rhizobacteria in relation to their capacity to solubilize soil phytates is by their genetic transformation with genes that codify for those enzymes. In this work, the gene phyL from B. licheni- formis was cloned into the suicide delivery vector pJMT6 (a derivative vector from the pUT/mini Tn5 system). The recombinant construction, which contains a non-antibiotic resistance selection marker, was transformed in Escherichia coliCC118λpir. A transformant clone (F16) was selected and further characterized. These results are a first step to develop improved growth promoting rhizobacteria as for the production of recombinant phytase activity, as alternative to reduce environmental pollution and to improve crops productivity.